Risk of Recurrence of Colon Polyps - Lyle G. Henry; Robert E. Condon; W Schulte; Charles Aprahamian; Jerome J. DeCosse (1975)
HENRY, LYLE G. M.D.; CONDON, ROBERT E. M.D.; SCHULTE, WILLIAM J. M.D.; APRAHAMIAN, CHARLES M.D.; DeCOSSE, JEROME J. M.D. Author Information